Poziom kompetencji matematycznych dzieci kończących edukację przedszkolną w systemie Montessori. Perspektywa badawcza - Kaiser, Izabella (Studia Edukacyjne, 2020)
The presented article discusses the issue of mathematical education in kindergartens that follow the Montessori education method. The basic assumptions of the educational system developed by M. Montessori have been discussed, with a special focus on mathematical education. The article presents the results of empirical research proving that children who complete their preschool education in the Montessori system demonstrate a high level of mathematical competencies as indicated in the Core Curriculum for Pre-school Education. The best results obtained by the examined children related to such competencies as counting objects, discriminating between correct and faulty counting, determining if two sets are equal in number, using ordinal numerals and spatial orientation tasks, including telling left from right, determining directions and the position of objects. The tasks that proved the most difficult for all the examined children were those related to temporal orientation. The diagnosed high level of mathematical competencies of children completing their pre-school education leads to the optimistic conclusion that mathematical education based on the principles of the Montessori system ensures educational effectiveness.